THE PROBLEM OF A MILITARY AND HISTORICAL REALITY - Шаколюкова, В. Д. (Proceedings of the Kyiv Aviation Institute. Series: Philosophy. Cultural, 2015)
The article is dedicated to the study of a reality problem and the objectivity of tuition of military and historical material under conditions of the modern society. Value principles of the given problem are defined.